Promotion of Bening Skincare Interest on Social Media - Frans Sudirjo; Mutmainah Mutmainah; Ramadhani Hamzah; Yuliana Yuliana; Jenneke Widya M. Maasi (Jurnal Mirai Management, 2023)
This study sought to ascertain the impact of eWOM, expenses, and online media on consumer interest in purchasing Bening skin care.This testing method makes use of numbers.Important information is the information source for this study.Providing respondents with a poll in the form of questions with Likert scale responses is important information employed.Likert scale with five options available.With a student focus, Maranatha University serves as the population source.Purposive testing was employed in this study's testing procedure with a total sample size of 92 respondents.Fractional results reveal that while cost and ewomen greatly influence purchase interest in Bening skin care, online media promotion does not fundamentally affect such interest.The findings maintain that pricing, eWOM, and Webbased media advertising have a significant impact on consumers' intentions to purchase Bening skin care. Keywords : E-wom; Price; Buying interest; Social media promotion